2010
DOI: 10.1179/146141010x12640787648694
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for long-term averaging of strontium in bovine enamel using TIMS and LA-MC-ICP-MS strontium isotope intra-molar profiles

Abstract: . (2010) 'Evidence for long-term averaging of strontium in bovine enamel using TIMS and LA-MC-ICP-MS strontium isotope intra-molar proles.', Environmental archaeology., 15 (1). pp. 32-42. Further information on publisher's website:http://dx.doi.org/10.1179/146141010X12640787648694Publisher's copyright statement:Additional information: Visit Maney's website at http://www.maneypublishing.com Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…Furthermore, in some teeth, such as those of cattle, with extended enamel, maturation times strontium incorporated into tooth enamel may average dietary strontium over a prolonged time period. This makes such teeth particularly unsuitable for resolving migration with high temporal resolution (Montgomery et al, 2010). Nevertheless, the level of mobility in past populations remains a key archaeological question, even if the timescales of migration are yet to be accurately determined.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, in some teeth, such as those of cattle, with extended enamel, maturation times strontium incorporated into tooth enamel may average dietary strontium over a prolonged time period. This makes such teeth particularly unsuitable for resolving migration with high temporal resolution (Montgomery et al, 2010). Nevertheless, the level of mobility in past populations remains a key archaeological question, even if the timescales of migration are yet to be accurately determined.…”
Section: Introductionmentioning
confidence: 97%
“…Intratooth isotopic and chemical variability should be viewed as a source of further information, but could be problematic when trying to compare with either older datasets, or employing explanatory structures that rely on homogenizing multiple years of life. Montgomery and Evans (2006) and Montgomery et al (2010) recommended against the use of micro-sampling techniques because of difficulties in determining the extent of delay in the maturation of mineralization in different microstructures (i.e., striae of Retzius) and uncertainties of the relevance of intra-tooth variations. Studies using large animals (Britton et al, 2011;Montgomery et al, 2010) found that intra-tooth sampling could produce evidence for long-term averaging effects that result from the long-duration that some elements have within the body.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Montgomery and Evans (2006) and Montgomery et al (2010) recommended against the use of micro-sampling techniques because of difficulties in determining the extent of delay in the maturation of mineralization in different microstructures (i.e., striae of Retzius) and uncertainties of the relevance of intra-tooth variations. Studies using large animals (Britton et al, 2011;Montgomery et al, 2010) found that intra-tooth sampling could produce evidence for long-term averaging effects that result from the long-duration that some elements have within the body. One problem may be that studies focusing on a single tooth may lack broader applicability in terms of the relationship between body averages and mineral deposition or maturation rates.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…The approach has been used extensively on humans, but in recent years, methodological research (e.g. Madgwick et al 2012;Montgomery et al 2010b) and case studies (e.g. Bendrey et al 2009;Towers et al 2010;Viner et al 2010) have demonstrated the value of the method for examining the movement of domestic animals in Britain.…”
Section: Methodsmentioning
confidence: 99%